Patriarchy and its Enduring Challenge to Feminism in the Modern Age - Bellour, Leila (Milev Journal of Research and Studies, 2021)
This paper attempts to answer the momentous query whether modernity is gendered masculine or feminine. Despite modernity’s stinging criticism of Descartes’ Cartesian split, the male/female binary opposition seems to be invincible. This paper vindicates that modernity is gendered masculine despite women’s attempts to alter the shoreline of male dominance and transcend gender binaries. With the advent of modernity, the ossified patriarchal system proved difficult to fade away. The paper evinces the factors that affected gender identity in the modern age. These factors also helped preserve and shore up the traditional patriarchal ideologies.